2008
DOI: 10.1159/000156903
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Removal of Vestibular Schwannomas after Failed Previous Microsurgery

Abstract: Recurrent and regrowing large vestibular schwannomas (VSs) may require another microsurgical procedure. Little is known about the incidence and the consequences of this second surgical procedure. We reviewed our own 10 reoperated cases during a 20-year period. Eight of them were supposed to have a radical surgery at the initial step, while 2 had experienced a subtotal resection. The mean interval between the 2 surgeries was 8.3 years with an ultra-late recurrent case at 20 years. Additional surgery was justifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
1
13
1
Order By: Relevance
“…The median period between initial microsurgical resection and surgery for recurrence in our series was 79 months. This time interval is comparable to previous reports (6,13,28). Most articles on repeated surgical treatment have focused mainly on small or middle-sized tumors, whereas there are less data on large recurrent tumors.…”
Section: Surgical Resection After Previoussupporting
confidence: 87%
“…The median period between initial microsurgical resection and surgery for recurrence in our series was 79 months. This time interval is comparable to previous reports (6,13,28). Most articles on repeated surgical treatment have focused mainly on small or middle-sized tumors, whereas there are less data on large recurrent tumors.…”
Section: Surgical Resection After Previoussupporting
confidence: 87%
“…Compared with observations reported in previous studies of repeat resection of VS tumors, 10,12,23 the findings in the present study suggest that our patients may have had an enhanced rate of preservation of facial nerve function. The authors of 1 study noted that facial nerve function deteriorated in 5 (42%) of 12 patients who underwent a repeat resection; 3 (30%) of 10 patients with preoperatively good facial function (i.e., of an HB grade of I-II) developed reduced or absent facial nerve function (of HB Grade ≥ III).…”
Section: Neurological Outcomescontrasting
confidence: 50%
“…23 The largest study to date reported that 16 (46%) of 35 patients had worsening facial function 1 year after repeat surgery (1 patient's facial function was already HB Grade VI). Twelve (57%) of 21 patients with HB Grade I-II facial function at the time of revision surgery had deterioration of facial function.…”
mentioning
confidence: 99%
“…3 Repeat operation is also associated with an increased risk of complications, including poor facial nerve outcome-only 50% of patients preserve their good facial nerve function. 3,13 In cases in which GKS fails and microsurgical resection is required, facial nerve preservation is 52%, a significant drop from the expected chance of facial nerve preservation with either treatment alone. 14 Patients in whom initial treatment (either radiosurgery or microsurgery) failed, who are re-treated with radiosurgery for their residual tumor, have had better outcomes; 90% of patients with good facial nerve function prior to radiosurgery had preservation of their facial function.…”
mentioning
confidence: 99%